Pengembangan Aplikasi Game Edukasi Sejarah Sunan Kalijaga Berbasis Android - Vitianingsih, Anik Vega; Firmansyah, Anggi; Maukar, Anastasia Lidya; Choiron, Achmad; Cahyono, Dwi (JKTP: Jurnal Kajian Teknologi Pendidikan, 2023)
Historical education is essential in forming human character because it is the basis for forming a sense of nationalism. Along with the development of technology, learning models are also affected. Learning can be facilitated through learning sources other than educators, thereby changing the role of educators in learning and adapting learning to current developments. One of the learning resources is game technology. Game applications can be a learning medium because of their visual and interactive nature. Packing history learning into an educational game application might be an alternative source of learning that is interesting and not monotonous. The purpose of this research is developing education media as an Android-based historical learning tool by packaging the historical learning of the story of Sunan Kalijaga in the form of a game application. The results of the black box, white box trials that went well, and the feasibility test that was carried out on 15 respondents, 93% stated that the material presented was appropriate so that it can be concluded that the game application is suitable for use as an alternative media for mobile learning by teachers and students with an assessment feature using an Android smartphone.AbstrakPendidikan sejarah sangat penting dalam proses pembentukan karakter manusia karena merupakan dasar dari pembentukkan rasa nasionalisme. Seiring dengan berkembangnya teknologi, Pembelajaran pun ikut terpengaruhi. Pembelajaran dapat dipermudah melalui sumber pembelajaran selain pendidik, sehingga menggubah peran pendidik dalam pembelajaran dan menyesuaikan pembelajaran dengan perkembangan zaman saat ini. Salah satu sumber pembelajaran itu adalah teknologi game. Aplikasi game dapat menjadi media pembelajaran karena sifatnya yang visual dan interaktif. Mengemas pembelajaran sejarah kedalam sebuah aplikasi game edukasi mungkin bisa menjadi salah satu alternatif sumber pembelajaran yang menarik dan tidak monoton. Tujuan dari penelitian ini adalah membuat aplikasi game “Lokajaya Sang Kalijaga” sebagai sarana pembelajaran sejarah berbasis Andoid dengan mengemas pembelajaran sejarah kisah Sunan Kalijaga ke dalam bentuk aplikasi game. Hasil dari uji coba black box, white box yang berjalan baik serta uji kelayakan yang telah dilakukan pada 15 responden, 93% menyatakan materi yang dibawakan telah sesuai sehingga dapat disimpulkan aplikasi game layak dipergunakan sebagai media alternatif pembelajaran secara mobile oleh guru dan murid dengan fitur penilaian menggunakan smartphone Android.